2015
DOI: 10.1103/physreve.92.041003
|View full text |Cite
|
Sign up to set email alerts
|

Interface evolution during radial miscible viscous fingering

Abstract: We study experimentally the miscible radial displacement of a more viscous fluid by a less viscous one in a horizontal Hele-Shaw cell. For the range of tested injection rates and viscosity ratios we observe two regimes for the evolution of the fluid-fluid interface. At early times the interface length increases linearly with time, which is typical of the Saffman-Taylor instability for this radial configuration. However, as time increases, the interface growth slows down and scales as ∼t 1 2 , as one expects in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 72 publications
0
18
0
Order By: Relevance
“…Note that the propagation of multiple water fingers can also be observed in a smooth‐walled fracture (Hele‐Shaw cell) under the conditions of the limit of zero interfacial tension [ Bischofberger et al ., ; Chui et al ., ], i.e., the absence of capillary force. In this case, the number of fingers increases with the injection rate Q regardless of the viscosity ratio [ Chui et al ., ], which is consistent with our experimental observations (see Figures a, e, and i). Finally, the mean water‐filled aperture is smaller than that in the capillary fingering regime, which is clearly illustrated in Figures and .…”
Section: Resultsmentioning
confidence: 99%
“…Note that the propagation of multiple water fingers can also be observed in a smooth‐walled fracture (Hele‐Shaw cell) under the conditions of the limit of zero interfacial tension [ Bischofberger et al ., ; Chui et al ., ], i.e., the absence of capillary force. In this case, the number of fingers increases with the injection rate Q regardless of the viscosity ratio [ Chui et al ., ], which is consistent with our experimental observations (see Figures a, e, and i). Finally, the mean water‐filled aperture is smaller than that in the capillary fingering regime, which is clearly illustrated in Figures and .…”
Section: Resultsmentioning
confidence: 99%
“…For their experiments on miscible rectilinear flow through a relatively wide gap, Snyder and Tait (1998) argued that λ/b was insensitive to mobility ratio and that 1 λ/b 3. Chui et al (2015) suggest that there are two regimes for the evolution of the fluid-fluid interface. At early times, interface length increases linearly with time, which is typical of the Saffman-Taylor instability.…”
Section: Saffman-taylor Instabilitymentioning
confidence: 99%
“…Zimmerman & Homsy (1992) similarly suggested that the asymptotic behaviour may include multiple steadily propagating fingers under the assumption that tip splitting may balance the upwards cascade in the scale of the fingers, but were unable to extend their numerical simulations to a final state. In experiments in a radial geometry, Chui et al (2015) showed a transition in finger growth from a scaling with t to one with t 1 2 corresponding to the shutdown of the instability. However, the ultimate fate and final form of the fingers remains unclear.…”
Section: Introductionmentioning
confidence: 99%